Investigation of Deaths from Mushroom Poisoning at Tubburg Village, Wangban Sub-district, Phetchabun Frovince - Banyati, Phichet; Pongchamnapai, Phana; Jarasarn, Yuwarat; Srisook, Pornsit; Chaira-ngab, Tassaporn (Journal of Health Science of Thailand, 2017)
Many cases of mushroom poisoning were reported every year. Most of them were caused by consuming mushroom collected near their house or in the forest. The objective of this study was to investigate an outbreak of fatal mushroom poisoning at Tubburg Village, Wangban Sub-district, Phetchabun Province in order to confirm the diagnosis, the characteristic of the outbreak and set-up control and prevention measures. The incident was reported on 24 May 2012. Descriptive study was conducted by reviewing medical records, interviewing the patients and their relatives, reviewing the situation of diarrheal cases in the last 5 years, and finding additional mushroom poisoning cases as well as performing laboratory investigation on mushroom samples. The finding revealed 7 mushroom poisoning cases (morbidity 5.2 per 1,000 population), of whom 5 cases dies (case-fatality rate of 71.4%). The median of age of cases was 23 years old. All of the patients had abdominal pain, vomiting, diarrhea and paralysis. Jaundice was observed in 5 cases (71.4); and nausea in 3 cases (42.9%). These symptoms were correlated with the laboratory findings of Amanita sp-1, Amanita sp- 2, Clitocybe sp-1 which had alpha-amantin and muscarine that effected to liver, kidney and brain. This study also found that there was high level of Liver and Kidney function test in all of death cases. To prevent the villagers from the mushroom poisoning intake, the mushroom information must be informed with their pictures to ensure the villagers corrected understanding.